Structure and subjects of information policy - A. A. Ebzeev; O. A. Sudorgin; V. F. Nitsevich; O. A. Nesterchuk (Управление)
The article substantiates the importance of information policy for the sustainable development of the state and society. The analysis of the information policy structure and its formation within the framework of the international agenda is carried out, considering the interests of all countries. The requirements for the analysis of information policy and its concept on the basis of objects existing in the information space are determined. The main approaches to the definition of objects of information policy are revealed. The problem of the relationship between the state and society in the context of information policy is considered. The importance of the interaction of social and information systems and its influence on public opinion is substantiated. The concept of information policy subject is interpreted from the political science and philosophy point of view. The main difficulties in understanding this definition are highlighted due to the differences between social and information spaces. The main types of subjects in the political sphere that are actively involved in the political process, representing individual, group and institutional actors, are given. The influence of modern trends on the composition of political subjects is described. Types of information policy subjects analysis and classification are carried out. The use of the information space by terrorist and extremist organizations deprived of their official status for their own purposes is analyzed.